MINAT BELI PADA MARKETPLACE UNICORN DI INDONESIA : TOKOPEDIA DAN BUKALAPAK - Mar’atul Fahimah; Evi Mayanti Muyassaroh (Fakultas Ekonomi dan Bisnis, 2019)
Online sales (E-Commerce) in Indonesia are experiencing very rapiddevelopment. One of the factors that increasingly increases online sales is themarketplace that has high trust and credibility in the minds of consumers. Marketplaceplayers in Indonesia from domestic and abroad. From within the country who have beensuccessful as start ups who have reached the Unicorn level, namely Tokopedia andBukalapak. At present consumer behavior in shopping has undergone many changes.This study aims to analyze differences in buying interest in Tokopedia and Bukalapak.This research method is descriptive with comparative research types. The technique usedin sampling is accidental sampling. Independent Sample t-Test to determine differences inbuying interest. The results showed that the Tokopedia and Bukalapak marketplaces hadno difference in buying interest.